Diminished Frequencies of Cytotoxic Marker Expressing T- and NK Cells at the Site of Mycobacterium tuberculosis Infection - Kathamuthu, Gokul Raj; Moideen, Kadar; Sridhar, Rathinam; Baskaran, Dhanaraj; Babu, Subash (Frontiers in Immunology, 2020)
Tuberculous lymphadenitis (TBL) individuals exhibit reduced frequencies of CD8+ T cells expressing cytotoxic markers in peripheral blood. However, the frequencies of cytotoxic marker expressing CD4+, CD8+ T cells and NK cells at the site of infection is not known. Therefore, we measured the baseline and mycobacterial antigen specific frequencies of cytotoxic markers expressing CD4+, CD8+ T cells and NK cells in the LN (n=18) and whole blood (n=10) of TBL individuals. TBL LN is associated with lower frequencies of CD4+ T cells expressing cytotoxic markers (Granzyme B, CD107a) compared to peripheral blood at baseline and in response to PPD, ESAT-6 and CFP-10 antigen stimulation. Similarly, lower frequencies of CD8+ T cells expressing cytotoxic markers (Perforin, Granzyme B, CD107a) were also present in the TBL LN at baseline and following [except perforin] antigen stimulation. Finally, at baseline and after antigen (PPD, ESAT-6 and CFP-10) stimulation, frequencies of NK cells expressing cytotoxic markers were also significantly lower in TBL LN compared to whole blood. Hence, TBL is characterized by diminished frequencies of cytotoxic marker expressing CD4+, CD8+ T cells and NK cells at the site of infection, which might reflect the lack of protective immune responses at the site of Mycobacterium tuberculosis infection.